Rise of use effectiveness of solar energy in solar systems - Voznyak, O.; Dacko, O.; Shapoval, S. (Видавництво Львівської політехніки, 2013)
This article coves the results of investigation of solar radiation incoming on the solar collectors. Dependence between the amount of discreet orientations of the solar collector and efficiency of work of its system has been established. The results of the experimental researches of one constant and four variable orientations of the collector on the Sun are given. The dependence between different orientations of the absorber and different constructional overall dimensions are determined. It is shown that we can receive more energy from triple orientation collectors than from traditionally flat. Подано результати досліджень надходження сонячного випромінювання на сонячні колектори. Отримано залежність між кількістю дискретних орієнтацій та ефективністю роботи даної системи. Подано результати експериментальних досліджень стаціонарних та дискретноорієнтованих сонячних колекторів відносно сонячного випромінювання. Встановлено залежності між різними орієнтаціями теплопоглинача і ефективністю роботи геліосистеми. Показано, що із дискретноорієнтованих сонячних колекторів мож на отримати більше енергії, ніж із стаціонарних.
Keywords: solar collector; discreet orientation; solar energetic; сонячний колектор; дискретна орієнтація; сонячна енергетика